Mekanisme Operasional Kaleng NU di Lembaga Amil Zakat Infaq Shodaqoh Nahdlatul Ulama’ (LAZISNU) - Muzzaki, Ahmad; Rosyidah, Irma (Journal of Industrial and Syariah Economics, 2023)
This article was written to review the operational Mechanism of Kaleng Nu at the Amil Zakat Infaq Shodaqoh Nahdlatul Ulama Institution (Lazisnu). The type of research used in this research is a literature review. The purpose of writing this article is to explain the Operational Mechanism of Kaleng Nu at the Amil Zakat Infaq Shodaqoh Nahdlatul Ulama' (Lazisnu) Institution so that it is beneficial for the people and the poor. The research method used in writing this article is qualitative descriptive, by presenting theoretical studies and existing sources and presented in the form of a description. NU D Can Operational Mechanismith The way to pick up the ball is to go directly to the house muzakki. Collection of zakat, infaq, and alms is carried out once a month by collecting at the donor's house by providing a muzakki savings book as proof of monthly donor payments.